Characterization of Palm-Based Binary Fat Blends and Development of Margarine from the Blends - Saadi, Sami. (2010)
The main objectives of this study were: (1) to determine the effect of stearin excess and small dose of monoacylglycerol (an emulsifier) on thermal behavior, solid fat content and microstructure properties of PO based margarine fats, and (2) to assess the changes in the physicochemical and rheological properties of water-in-oil (w/o) emulsion systems during the storage time taking multipurpose margarine (MPM) as an example. The ability of palm oil (PO) to crystallize as beta prime polymorph has made it as an attractive option for the production of margarine fat (MF). Palm stearin (POs) expresses similar crystallization behavior, and is considered one of the best substitutes of hydrogenated oils due to its capability to impart the required level of plasticity and body to the finished product. Normally, POs is blended with PO to reduce the melting point at body temperature (37°C), Lipid phase, formulated by PO and POs in different ratios, were subjected to an emulsification process and the following analyses were done: triacylglycerol (TAG), solid fat content (SFC) and thermal behavior. In addition, iodine value (IV), fatty acid composition (FAC) and rheological properties including viscosity () and shear stress () were determined in before emulsification process (BEP), while the microstructure properties including size and number of crystals were also determined for experimental and commercial margarine fats (EMF and CMF) after emulsification process (AEP). Results showed that blending and emulsification at POs level over 40% (w/w) were significantly changed the physicochemical and microstructure properties of EMF as compared to CMF, resulting in a desirable PPO/POP% of less than 36.1%. SFC at 37 ºC, crystal size, crystal number, crystallization and melting enthalpies (H) were 15%, 5.37μm, 1425 crystal/μm2, 17.25 J/g and 57.69 J/g, respectively. Differential scanning calorimetry (DSC) analysis of blends indicated significant effect on temperature transition; peak sharpness and enthalpy at POs level more than 40% (w/w). The continuous incorporation of POs in the fat matrix system of lipid phase of BEP and AEP showed the apparition of new peaks at high temperature level ranging from 50 to 56 °C. These peaks were attributed to the higher melting compounds of TAGs and the occurrence of polymorphic transition. The pNMR showed the formation of eutectic systems at POs over 40% (w/w), resulting in low level of SFC of less than 15% at body temperature (37 °C). All data reported indicate that the formation of granular crystals in margarine fat was dominated by high melting TAG namely PPO/POP, whilst the small dose of monoacylglycerol that is used as emulsifier slowed the emergence of undesirable polymorph in EMF as compared to CMF. The assessment of binary blend behavior of PO/POs based water-in-oil (w/o) emulsions during the storage time showed significant changes for total physicochemical and rheological properties of (w/o) emulsion types, resulting in SFC at 28 °C, consistency,softness and storage modulus (G') of less than 25%, 16 Kg f/cm2, 30 mm ease of cone penetration and 15x104 Pa, respectively. These data provide an indication on the weakness structure network and low workability force of the MPM models over 40% (w/w) of POs. Examination microscopy of the images revealed that the incorporation of PS levels more than 40% (wt./wt.) have the ability to readily transform beta prime polymorph (') to beta (), while the reduction of PS over 40% (wt./wt.) slowed down the emergence of polymorph. Meanwhile, PV and FFA of 2 Meq O2/Kg and 0.35% respectively, screened excellent oxidative stability and high resistance against acidity and rancidity of multipurpose margarine (MPM). This oxidative stability in MPM models during the storage time may explain by the presence of an optimal average of saturated bonds that made them to be chemically more stable against oxidative deterioration.